David vs. Goliath (Case Planned Parenthood and the selling of aborted baby body tissues) : The slippery slope of abortion legalization - Palacios Yabar, Mirielle Liliana (2018)
After the legalization of the constitutional right of women to abortion in the United States with the case Roe vs. Wade, the door was opened to many consequences that this decision brought with it. One of these consequences is the illegal sale of organs and tissues extracted in abortions. In the present article a bioethical and biolegal analysis will be developed of the case that brought to light that slippery slope of the legalization of abortion, this is the case of the research of the non-profit organization, Center for Medical Progress (CMP) to the multinational abortion, Planned Parenthood, and the consequent investigation and final report presented by the Select Panel of the Committee on Energy and Commerce of the US House of Representatives.